The composition and ultrastructure of sorghum spent grains. Issue 1 (14th June 2013) - Holmes, Calum P.; Cahill, Gearoid; Smart, Katherine A.; Cook, David J.
Abstract : The present study aimed to investigate the composition and structure of sorghum spent grains (SSG) as a pre‐requisite for evaluating potential applications of this brewery co‐product. SSG samples sourced from African breweries employing a grist with a proportion of a hammer milled‐unmalted sorghum ( Sorghum vulgare cv. Fara Fara) were found to be heterogeneous materials containing remnants of intact grains, and with particles ranging in size from <0.1 to >2 mm. Samples contained a considerable amount of residual starch (4.6–10.0% d.b.), much higher than typically reported for barley‐derived spent grains. This probably arises from the use of grists high in unmalted sorghum, but indicates that improvements in brewing process efficiency could be achieved with improvements, for example, in milling and mashing protocols. The crude protein content of the SSG samples was unexpectedly high (38.0–41.2% d.b.), indicating that this material would have potential value as an animal feed or source of refined protein. Potential reasons for this higher than expected residual protein content are discussed. The remainder of SSG gross composition (mean of five samples) was cellulose (11.4% d.b.), hemicellulose (17.3% d.b.), lipid (8.5% d.b.), lignin (9.4% d.b.) and ash (4.46% d.b.), with a total mass recovery of close to 98% represented by all analysed components. Copyright © 2013 The Institute of Brewing & Distilling